2023
DOI: 10.1111/1759-7714.14778
|View full text |Cite
|
Sign up to set email alerts
|

Higher aorta dose increased neutrophil‐to‐lymphocyte ratio resulting in poorer outcomes in stage II‐III non‐small cell lung cancer

Abstract: Background This study focused on the relationship between the neutrophil‐to‐lymphocyte ratio (NLR) and the dose of organs at risk in patients with stage II–III non‐small cell lung cancer (NSCLC) receiving intensity‐modulated radiotherapy. Methods The clinical characteristics and dosimetric parameters of 372 patients were collected retrospectively. A high NLR was defined as that ≥1.525. Survival analysis was conducted using the Kaplan–Meier and Cox regression analysis. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Li et al reported that a low NLR predicted better PFS and OS, and aorta V10 was significantly associated with a high NLR. 29 In one study, factors such as baseline counts, heart V20, V40, or mean body dose (MBD) were predictors of NLR or PLR 1 month after RT. 26 In radiation therapy oncology group (RTOG) 0617 it was elucidated that V5, V30, and V40 Gy of the heart correlated with survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al reported that a low NLR predicted better PFS and OS, and aorta V10 was significantly associated with a high NLR. 29 In one study, factors such as baseline counts, heart V20, V40, or mean body dose (MBD) were predictors of NLR or PLR 1 month after RT. 26 In radiation therapy oncology group (RTOG) 0617 it was elucidated that V5, V30, and V40 Gy of the heart correlated with survival.…”
Section: Discussionmentioning
confidence: 99%
“…There were several studies about the correlation between dose distributions 27 and doses to specific structures 28,29 and radiation‐induced dynamic changes in immune cells. Li et al reported that a low NLR predicted better PFS and OS, and aorta V10 was significantly associated with a high NLR 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the predictive value of NLR for the prognosis of LA-NSCLC needs further exploration especially in the era of immunotherapy. In NSCLC patients with stage II and stage III who received radical intensity-modulated radiation therapy, prior research has shown that a lower baseline NLR indicates higher rates of PFS and OS 15 . Conversely, baseline NLR was confirmed to have no association with OS in III NSCLC patients, of whom 115 (35%) patients underwent surgical resection, followed by chemotherapy or chemoradiotherapy, and the remaining 217 (65%) patients received synchronous CRT 16 .…”
Section: Discussionmentioning
confidence: 99%